Perceptions of Mosque Teenagers About Instagram Content the Influence of the Dangers of Dating and Motivation for Early Marriage: Persepsi Remaja Masjid Tentang Konten Instagram Pengaruh Bahaya Pacaran dan Motivasi Pernikahan Dini - Raharjo, Rico Widoseno; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this research is to find out the perception of Baitul Izzah Mosque Youth about Instagram content @indonesiawithout dating (case study) the effect of the dangers of dating and early marriage motivation. Respondents in this study found 14 active members of the Baitul Izzah Mosque Youth. Researchers used qualitative descriptive methods and also direct interviews with Focus Group Discussions. The results of this study are that five mosque youth members agree or are positive with the content of Instagram @indonesiawithout dating because most of them also follow the account, five youth members of the mosque disagree or are negative about the content of the Instagram account @indonesiawithout dating and four others are still hesitant to comment on the account @indoensiwithout dating. . There was also an agreement during the Focus Group Discussion that the post posted by the Instagram account @indonesiawithout dating is mooton, the account should display videos of famous usd lectures that are familiar to teenagers today.